Targeted therapy for soft tissue sarcomas in adolescents and young adults - Steppan, Diana A (Adolesc Health Med Ther, 2017)
Soft tissue sarcomas (STSs) are a heterogeneous group of tumors originating from the mesenchyme. Even though they affect individuals in all age groups, the prevalence of subtypes of STSs changes significantly from childhood through adolescence into adulthood. The mainstay of therapy is surgery, with or without the addition of chemotherapy and/or radiation therapy. These treatment modalities are associated, in many cases, with significant morbidity and, given the heterogeneity of tumor histologies encompassed by the term “STS”, have not uniformly improved outcomes. Moreover, some subgroups of STSs appear to be more, and others less, responsive to conventional chemotherapy agents. Over the last two decades, our understanding of the biology of STSs is slowly increasing, allowing for the development of more targeted therapies. We review the new treatment modalities that have been tested on patients with STSs, with a special focus on adolescents and young adults, a group of patients that is often underrepresented in clinical trials and has not received the dedicated attention it deserves, given the significant differences in biology and treatment response in comparison to children and adults.